"Winter recess" - Pryor, Geoff, 1944- (1981)
It is the mid-year parliamentary recess and many MP's can be seen flying north to sunnier climes on various 'study tours', which kind of makes you wonder when politicians in the northern hemisphere are probably doing the same thing.--Information provided by Geoff Pryor.
Title devised by cataloguer.
Published in the Canberra Times on 14 June 1981.
Part of the Pryor collection of cartoons and drawings.
Also available online
Keywords: Politicians -- Australia -- Caricatures and cartoons; Australia -- Politics and government -- 1976-1990 -- Caricatures and cartoons; Federal politicians